The neural mechanisms for the recognition of face identity in humans - Anzellotti, Stefano; Caramazza, Alfonso (Frontiers in Psychology, 2014)
Every day we encounter dozens of people, and in order to interact with them appropriately we need to recognize their identity. The face is a crucial source of information to recognize a person's identity. However, recognizing the identity of a face is challenging, because it requires to distinguish between very similar images (e.g. the front views of two different faces) while recognizing that very different images (e.g. a front view and a profile) can depict a same person. Neuroimaging has the whole-brain coverage needed to investigate where representations of face identity are encoded, but it is limited in terms of spatial and temporal resolution. In this article, we review recent neuroimaging research that attempted to investigate the representation of face identity, the challenges it faced, and the proposed solutions, to conclude that given the current state of the evidence the right anterior temporal lobe is the most promising candidate region for the representation of face identity.